Procladius (Diptera, Chironomidae) of Europe and a global view - Brodin, Yngve (Zootaxa, 2025)
A project initiated in 1991 to untangle species-taxonomy of European Procladius (Chironomidae) has been accomplished. Increasing amount of material, loans and especially the development of barcodes and the BIN-system of BOLD, made finalization possible after about 33 years. An iterative process based on detailed studies of male morphology and barcode clusters, BINs, resulted in identification of 27 species present in Europe, most of them also in Asia (China, Japan, Mongolia and Russia) and North America (Canada and the United States). One hundred morphological characters were adopted for species identification of which the 30 most important ones were used to construct a species key and an additional helpdesk. The key contains three characters for each species separation as this is frequently needed for reliable identification. The ratio GspR, the outer length of the gonostylus process versus length of outer margin in gonostylus, proved to be the most important character for species identification. All but two of the 27 species have barcodes and BINs. All but one BIN contained only one species. The exception is a BIN that previously was divided into two BINs each containing one morphologically distinct species. Intraspecific divergence within the species ranged from 0‒3.3% and interspecific divergence from 2.0‒8.8%. Four new species are presented. These are P. exilis Brodin, new species, P. gemma Brodin, new species, P. saeticubitus Brodin, new species and P. tenebricosus Brodin & Hellberg, new species. The other 23 species presented are as follows with new synonyms within brackets: P. appropinquatus (Lundström, 1916) [P. ruris Roback, 1971], P. bellus (Loew, 1866) [Tanypus rufovittatus van der Wulp, 1874, P. latifrons Kieffer, 1922, P. leucocoma Kieffer, 1922, P. profundorum Kieffer, 1923], P. breviatus Remmert, 1953, P. choreus (Meigen, 1804) [Chironomus incomptus Walker, 1856], P. clavus Roback, 1971, P. crassinervis (Zetterstedt, 1838) [Tanypus pectinatus Kieffer, 1909, P. bifasciatus Goetghebuer, 1936, P. cinereus Goetghebuer, 1936, P. abetus Roback, 1971], P. culiciformis (Linnaeus, 1767) [Tanypus sagittalis Kieffer, 1909, Trichotanypus scapularis Kieffer, 1924, P. freemani Sublette, 1964 in part], P. dentus Roback, 1971, P. ferrugineus (Kieffer, 1918) [Trichotanypus parvulus Kieffer, 1918, Trichotanypus fulvus Kieffer, 1924, Trichotanypus profundorum Kieffer, 1924, P. rugulosus Saether 2010], P. fimbriatus Wülker, 1959, P. flavifrons Edwards, 1929, P. floralis Kieffer, 1915, P. frigidus (Holmgren, 1869) [P. gretis Roback, 1971], P. imicola Kieffer, 1922 [P. bathyphilus Kieffer, 1922, P. nietus Roback, 1971], P. islandicus (Goetghebuer, 1931) [P. fuscus Brundin, 1949, P. vesus Roback, 1971], P. longistilus (Kieffer, 1916) [P. suecicus Brundin, 1949], P. lugens Kieffer, 1915 [P. macrotrichus Roback, 1971], P. lugubris (Zetterstedt, 1850) [P. barbatus Brundin, 1949, P. johnsoni Roback, 1980], P. nudipennis Brundin, 1947, P. pruinosus (Kieffer, 1924), P. signatus (Zetterstedt, 1850) [Trichotanypus nigriventris Kieffer, 1924, P. denticulatus Sublette, 1964 in part], P. simplicistilus Freeman, 1948, P. tatrensis Gowin, 1944. In addition, 12 species of Procladius not found in Europe are briefly described and it is indicated where they appear in the species-key. Species of Procladius have been reported from 133 countries or autonomies worldwide. As many as 12 species have been found in extreme cold places of the northern hemisphere, with mean annual temperature ‒10 C or more. Altitude records are at 4 730 m above sea level in the Himalayas. Larvae of most European species are known to be omnivorous, although predation might be more beneficial for growth. Synonyms and dubious names reduce the number of valid (accepted) species of Procladius according to Catalogue of Life and Systema Dipterorum with 34% worldwide. After the inclusion of four new species of the present study and two others from Asia the number or valid species of Procladius worldwide land on 69.